2021
DOI: 10.1111/ene.14706
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between retinal layer thickness and brain volumes in the UK Biobank cohort

Abstract: Background and purpose Current methods to diagnose neurodegenerative diseases are costly and invasive. Retinal neuroanatomy may be a biomarker for more neurodegenerative processes and can be quantified in vivo using optical coherence tomography (OCT), which is inexpensive and noninvasive. We examined the association of neuroretinal morphology with brain MRI image‐derived phenotypes (IDPs) in a large cohort of healthy older people. Methods UK Biobank participants aged 40 to 69 years old underwent comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 61 publications
5
38
1
Order By: Relevance
“…These reports suggest retinal neurodegeneration reflects cerebral neurodegeneration, and this mechanism may occur simultaneously. Importantly, prior reports (Ong et al, 2015;Mutlu et al, 2017;Chua et al, 2021) suggested that the retinal sublayer thicknesses reflect the cerebral microstructure (white matter and gray matter microstructure). The brain and retina share many characteristics, including similar microvasculature, embryology, and precise neuronal cell layers; axons from the optic nerve form a direct link, through the optic head, between the retina and the brain, thus, it is suggested that damage in the brain is associated with retinal thinning (especially for peripapillary RNFL and macular GCL) (Cabrera DeBuc et al, 2017;Kwapong et al, 2018;Mutlu et al, 2018).…”
Section: Introductionmentioning
confidence: 92%
“…These reports suggest retinal neurodegeneration reflects cerebral neurodegeneration, and this mechanism may occur simultaneously. Importantly, prior reports (Ong et al, 2015;Mutlu et al, 2017;Chua et al, 2021) suggested that the retinal sublayer thicknesses reflect the cerebral microstructure (white matter and gray matter microstructure). The brain and retina share many characteristics, including similar microvasculature, embryology, and precise neuronal cell layers; axons from the optic nerve form a direct link, through the optic head, between the retina and the brain, thus, it is suggested that damage in the brain is associated with retinal thinning (especially for peripapillary RNFL and macular GCL) (Cabrera DeBuc et al, 2017;Kwapong et al, 2018;Mutlu et al, 2018).…”
Section: Introductionmentioning
confidence: 92%
“…Optical coherence tomography (OCT) provides fast, noninvasive retinal imaging. 15 Thickness of the macular ganglion cell and inner plexiform layer (mGCIPL) correlates with brain volume measures in the general population 16 and in patients with MS. 14 Retinal atrophy, independent of damage inflicted by optic neuritis, occurs from the early stages of disease 15,17 and correlates with MS disability scores. 18,19 Because smoking and alcohol consumption are correlated behaviors, 20,21 it is difficult to disentangle their respective effects.…”
Section: Introductionmentioning
confidence: 99%
“…As an extension of the brain and sharing the same embryological origin with the CNS. Chua et al (2020) , Kashani et al (2021) , the retina is widely regarded as an accessible source for studying neurodegenerative and vascular injury processes occurring in the CNS ( Hart et al, 2016 ; Mutlu et al, 2018 ). Consistently, there has also been intense interest in using retinal imaging technology to understand, diagnose, and monitor neurological diseases ( Kashani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%